(untitled) (Research, Society and Development, 2021)
There is a close relationship between what the children are able to learn (cognitive) and what they are able to achieve (motor). Psychomotor interventions aim the development of specific motor skills, and it can positively influence learning difficulties. Thus, the aim of this review was to identify strategies to assess motor performance in children with learning difficulties. For this, an integrative review was carried out in the PubMed, Lilacs and Scielo databases, using the keywords. From a total of 244 records, 5 articles met the inclusion criteria in this review. Several studies were excluded because the learning disability is related to neurodevelopmental disorder or neurological disorders. The assessment strategies found were: fine motor, global, balance, spatial and temporal organization, laterality and body scheme tasks, writing assessment, reading and arithmetic. Conclusion: the assessment of motor skills is well described as a preventive and effective strategy to alleviate learning difficulties in children with learning disabilities.